2020
DOI: 10.3390/ma13225201
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of 60-Year-Old Sluice Gate Affected by Long-Term Operation

Abstract: Technological units of water reservoirs and power plants include sluice gates which are designed to completely seal the inflow or outflow of water in supply or discharge channels. This article describes the issue of technical assessment of a sluice gate made in the 1950s. Such structures are characterised by states of significant corrosive wear, permanent deformations of contact and sealing surfaces as well as increased levels of residual stresses. In such cases, it is difficult to determine service life using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For that reason, the authors reversed the standard approach and, thus, verified the experimentally obtained results by numerical analysis. Such an approach has already been used by the authors, and the results obtained were published in several scientific publications, e.g., [ 36 , 37 , 38 , 39 ]. Moreover, in conventional quantification of residual stresses by the hole-drilling technique the FEA is usually used, e.g., the correlation parameters used in the formulas for the computation of stress components from the relieved strains are determined mainly in a numerical way.…”
Section: Resultsmentioning
confidence: 99%
“…For that reason, the authors reversed the standard approach and, thus, verified the experimentally obtained results by numerical analysis. Such an approach has already been used by the authors, and the results obtained were published in several scientific publications, e.g., [ 36 , 37 , 38 , 39 ]. Moreover, in conventional quantification of residual stresses by the hole-drilling technique the FEA is usually used, e.g., the correlation parameters used in the formulas for the computation of stress components from the relieved strains are determined mainly in a numerical way.…”
Section: Resultsmentioning
confidence: 99%
“…In the experiment, four samples with different cladding techniques were prepared, then the samples were heat treated and machined. Residual stress levels were determined on the samples prepared in this way by the hole drilling method, which is one of the semi-destructive experimental methods, and the authors have extensive experience with it [13][14][15][16]. The lifetime of the die matrices made of steel alloys is approximately 100,000 cycles and can be increased by heat treatment, thin coating, or cladding [9].…”
Section: Introductionmentioning
confidence: 99%
“…Maierhofer C et al [9] investigated the use of radar and ultrasonic pulses to detect the operational safety of old sluice gates and showed that it can non-destructively detect the internal conditions of sluice sidewalls and concrete footings. Pástor M et al [10] performed numerical simulations of gates and determined the critical stress values at the location of reinforcement units and corrected them to reduce the stress values by about 15%. Sunu P W et al [11] developed a model for the flood control system of sluice gates and applied it well to the flood control monitoring system of sluice gates.…”
Section: Introductionmentioning
confidence: 99%